Chemical composition and protective effect of Juniperus sabina L. essential oil against CCl4 induced hepatotoxicity - Maged S. Abdel-Kader; Gamal A. Soliman; Mohammed H. Alqarni; Abubaker M. Hamad; Ahmed I. Foudah; Saleh I. Alqasoumi (Elsevier, 2019)
The hepatoprotective activity of the total extract of Juniperus sabina L. against CCl4 induced toxicity in experimental animals was previously reported and indicated promising results. Essential oil of J. Sabina was prepared by hydrodistillation method. Components of the oil were identified by comparison of GC-MS and retention indexes with reported data. The hepatoprotective effect of the essential oil against CCl4 induced toxicity was studied using male Wistar rats and silymarin at 10 mg/kg p.o as standard drug. The protective effect was evaluated via serum biochemical parameters such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma glutamyltranspeptidase (GGT), and total bilirubin as well as tissue parameters including non-protein sulfhydryl groups (NP-SH), malonaldehyde (MDA) and total protein (TP). Histopathological study was applied on the liver tissues using Mayer's hematoxylin stain, Periodic Acid Schiff - Hematoxylin (PAS-H) and Masson trichrome technique on light microscope. Electron microscope images were also obtained for more detailed study. Keywords: Juniperus sabina, Hepatoprotective, Essential oil, Biochemical parameters, Electron microscope